Selective Modulation of K+ Channel Kv7.4 Significantly Affects the Excitability of DRN 5-HT Neurons - Zhao, Chen; Su, Min; Wang, Yingzi; Li, Xinmeng; Zhang, Yongxue; Du, Xiaona; Zhang, Hailin (Frontiers in Cellular Neuroscience, 2017)
The serotonin (5-HT) system originating in the dorsal raphe nucleus (DRN) is impli-cated in various mood- and emotion-related disorders, such as anxiety, fear and stress. Abnormal activity of DRN 5-HT neurons is the key factor in the development of these disorders. Here, we describe a crucial role for the Kv7.4 potassium channel in modu-lating DRN 5-HT neuronal excitability. We demonstrate that Kv7.4 is selectively ex-pressed in 5-HT neurons of the DRN. Using selective Kv7.4 opener fasudil and Kv7.4 knock-out mice, we demonstrate that Kv7.4 is a potent modulator of DRN 5-HT neu-ronal excitability. Furthermore, we demonstrate that the cellular redox signaling mechanism is involved in this 5-HT activation of Kv7.4. The current study suggests a new strategy for treating psychiatric disorders related to altered activity of DRN 5-HT neurons using K+ channel modulators.